Socio-Economic Determinants of Credit Access in Micro Enterprises Household of East Java During New Normal Era - Christiayu Natalia; FX Gugus Febri Putranto (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2022)
The lack of micro-enterprises household in East Java that access business credit can affect the integration of MSMEs in the Global Value Chain (GVC) and exports acceleration in new normal era. This study aims to analyze the socio-economic determinants of microenterprise household credit access in East Java, and specific to each Bakorwil. Multinomial logistic regression analysis on the Susenas March 2021 and Potensi Desa 2021 found that there were differences in socio-economic characteristics in each Bakorwil. Important issues in accessing KUR/KUBE/KUB are poverty status, social protection programs, entrepreneur status, and internet use. Regional-based policies can be applied for business development and encourage integration into GVC by considering the socio-economic characteristics of each Bakorwil